EDITED BY THE RULES FÉDÉRATION INTERNATIONALE DE FOOTBALL ASSOCIATION (FIFA) FOR WORLD CUP 2014 AND CONFLICT WITH BRAZILIAN LAW (Fiep Bulletin - online, 2014)
We are one year of the World Cup 2014 in Brazil, one FIFA event, which featured backing of the Brazilian Government, and support of a large part of the population in the hope that through a major event infrastructure services suffer improvements, areas such as education, health and transport could gain in quality, benefiting both tourists and leaving a legacy to the children of these lands. But it is not what is happening, the scenario is established is to work in stages with the initial budget being modified, and improvements to the population being left out. After the enactment of the General Law of the Cup it portrays what is the evidence of a contract made between the Brazilian government and FIFA true benefited in every way , to have their demands fulfilled at any cost and thus confronting national sovereignty , the status the fans , releasing alcohol in stadiums , the status of the elderly , to limit the purchase of discounted tickets in a single sector , making no mention of the Consumer Protection Code , and at some points proving to be unconstitutional.
Keywords: World Cup General Law; Sports Law; Constitution.